Estimation of shrinkage deformations of masonry by determining cracking of internal building walls/Mūro susitraukimo deformacijų įvertinimas, analizuojant pastatų vidinių sienų supleišėjimą - Marčiukaitis, Gediminas (Journal of Civil Engineering and Management, 2000)
In practice a lot of cases are found, that loadbearing masonry walls of buildings are cracked. The main reason of these cracks is reinforced or metal lintel, reinforced concrete floors, waist-band and other elements. They impede free shrinkage deformation of masonry. In masonry, tension stresses appear and compression stresses, in impedemental elements. The formulas for calculation of these stresses and strains are suggested in the article. Analysis of this formulas show that stresses-strains depend on the ratio of areas of sections and the modulus of elasticity of masonry walls and impedimental structures or elements. It is important to evaluate the shrinkage of masonry and its further development. Such shrinkage begins before mounting other structures on walls. There are suggested methods and formulas for estimating changes of shrinkage deformations in time. Limiting shrinkage deformations are suggested according to the recommendations of Eurocodes 6. Theoretical and experimental results of changing of masonry shrinkage are compared. The comparison shows good agreement of these results. The suggested methods allow to choose such materials for masonry and time of mounting of other structures, which decrease the tension stresses in masonry because of its shrinkage and give opportunities to decrease danger of appearing cracks in walls or to avoid them, in general. Article in Lithuanian. First Published Online: 26 Jul 2012